Food security in the global age : South Asian dilemma - Adhikari, Ratnakar; South Asia Watch on Trade, Economics, and Environment (Kathmandu : South Asia Watch on Trade, Economics and Environment, 2001)
Contributed papers presented at various seminars.
P.B
Includes bibliographical references.
Keywords: Food supply -- South Asia -- Congresses; Scarcity